2014
DOI: 10.1016/j.cortex.2013.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive induction of plasticity in the human cortex: Uses and limitations

Abstract: After the embargo period via non-commercial hosting platforms such as their institutional repository  via commercial sites with which Elsevier has an agreement In all cases accepted manuscripts should: link to the formal publication via its DOI  bear a CC-BY-NC-ND license -this is easy to do, click here to find out how  if aggregated with other manuscripts, for example in a repository or other site, be shared in alignment with our hosting policy  not be added to or enhanced in any way to appear more like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 115 publications
0
31
0
Order By: Relevance
“…In particular, techniques such as transcranial magnetic stimulation (TMS) can be used not only to test the excitability of cortical networks, but also modulate excitability in a bidirectional and reversible manner when applied in trains of repetitive stimuli (i.e., repetitive TMS; rTMS) (Vallence and Ridding, 2014). The changes in excitability induced by rTMS are likely due to processes similar to the long-term potentiation (LTP) and long-term depression (LTD) described in animal models (Huang et al, 2007;Teo et al, 2007), which are key neural mechanisms involved in learning and memory (Cooke and Bliss, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, techniques such as transcranial magnetic stimulation (TMS) can be used not only to test the excitability of cortical networks, but also modulate excitability in a bidirectional and reversible manner when applied in trains of repetitive stimuli (i.e., repetitive TMS; rTMS) (Vallence and Ridding, 2014). The changes in excitability induced by rTMS are likely due to processes similar to the long-term potentiation (LTP) and long-term depression (LTD) described in animal models (Huang et al, 2007;Teo et al, 2007), which are key neural mechanisms involved in learning and memory (Cooke and Bliss, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…CE is defined as any augmentation of core information processing systems in the brain underlying perception, attention, conceptualization, memory, reasoning and motor performance (Sandberg and Bostrom, 2006; Luber and Lisanby, 2014). Studies reported TMS-induced modulations and enhancements of brain functioning and neural processing involved in: language comprehension (Floel et al, 2008), learning and memory (Vicario et al, 2013), cortical plasticity improving learning (Vallence and Ridding, 2014), motor memory (Butefisch et al, 2004), working memory (Gaudeau-Bosma et al, 2013), memory (Gagnon et al, 2011; Blumenfeld et al, 2014), phonological memory (Kirschen et al, 2006), perception (Hamilton et al, 2013), perceptual discrimination (Luber and Lisanby, 2014), eye movements and visual search, (Gerits et al, 2011; Luber and Lisanby, 2014), attention (Cooper et al, 2004; Lee et al, 2013), reward behavior (Stanford et al, 2013), analogic reasoning (Boroojerdi et al, 2001), motor learning (Luber and Lisanby, 2014), consolidation of new skills (Boyd and Linsdell, 2009), visual awareness (Grosbras and Paus, 2003), activity of specific frequencies supporting functions of the brain (Rahnev, 2013), and Pavlovian conditioning (Luber et al, 2007). …”
Section: Discussionmentioning
confidence: 99%
“…More recently, these have been complemented with non-invasive brain stimulation (NIBS) techniques (Transcranial Magnetic Stimulation, TMS; transcranial Electrical Stimulation, tES). NIBS modulates sensorimotor performance and higher-level behavior in both neurologically unimpaired participants and brain-damaged patients (Miniussi & Vallar, 2011); they are capable of inducing shortlasting changes in the human cortex (Vallence & Ridding, 2014; this Special Section), and simulate changes occurring in brain damage this Special Section).…”
mentioning
confidence: 97%